FRI0382 Impact of Treatments on Major Immunologic Pathways in SLE Depends on Type I Interferon Signature: Analysis from Biomarkers of Lupus Disease (BOLD) Study. (10th June 2014) - Merrill, J.T.; Immermann, F.W.; Zhou, T.; O'Toole, M.; Whitley, M.; Hill, A.A.; Zhang, Y.; von Schack, D.; Reddy, P.S.; Masferrer, J.L.; Kamp, S.; Guthridge, J.M.; et al.
Abstract : Background: The BOLD study investigated biologic effects of commonly used immune suppressants (IS) on SLE patients (pts), evaluating the safety of withdrawing IS from stable pts in trials. We have reported (1) that this protocol was well tolerated and that many biomarkers and treatment effects varied with a novel 11-gene interferon (IFN) signature. Objectives: The current analysis will focus specifically on effects of standard SLE treatments on expression of BLyS, IL17RA, and IL23, components of two critical pathways recently linked to Type I IFN activity in several autoimmune diseases (2, 3). Methods: 103 active SLE pts were tested for impact of IS on immune variables. 41 pts entered a prospective phase with brief steroids, IS withdrawal, and serial blood sampling until flare. Protein expression was measured by xMAP multiplex panel (IL23A) or sandwich ELISA (BLyS). TLDA gene expression was evaluated with an ANCOVA model adjusting for RNA quality and medications. Results: Pts with high IFN signal (IFN HI), had much higher BLyS (TNFSF13B) gene expression (p=0.005) compared to others (IFN LOW) as well as higher BLyS protein (p=0.00018) and more likelihood of antibodies to dsDNA (p=0.001) SSA (p=0.0007) RNP (p=0.0001) and Sm (p=0.01). IL17RA gene expression was also higher in IFN HI vs LOW (p=0.009). IL23A RNA was not increased but IL23 (p19) protein was greater in IFN HI (p=0.02). IL17RA RNA was lower in pts on IS vs no IS - 1.23 fold for MTX (p=0.047) 1.4 fold for MMF (p=0.01) and 1.17 fold for AZA (p=0.08). In fact, the AZA impact was only on IFN HI (1.33 fold decrease, p=0.03) with no effect on IFN LOW. MMF and MTX effects were restricted to IFN LOW only (1.77 fold lower for MMF, p=0.004, and 1.30 fold lower for MTX, p=0.03). A trend for lower BLyS in pts on hydroxychloroquine (1.64 lower, p=0.09) was due only to IFN HI (3.6 fold lower p=0.001) with no impact on IFN LOW. BLyS and IL17RA gene expression was stable between baseline, improving, and flare visits in all pts and in IFN HI, but there was markedly increased BlyS RNA at the flare visit (off IS) in IFN LOW (2.4-fold increase from baseline, p=0.0003), reaching levels equivalent to IFN HI. Conclusions: This study confirms an association between BLyS, IL17 and Type I IFN signals in SLE pts. Impact on these pathways of standard treatments (which are often used interchangeably in clinic and may confuse clinical trial endpoints) differ in IFN HI vs LOW. This underscores the selective potential of immune modulators, which can hopefully be chosen or combined more strategically in the future. References: Merrill ACR 2013. Ambrosi European J Immunol 2012 42:2274. Vincent Arth Res and Ther 2013 15:R97. Disclosure of Interest: J. Merrill Grant/research support: Pfizer, Consultant for: Pfizer, F. Immermann Employee of: Pfizer, T. Zhou Employee of: former employee of Pfizer, M. O'Toole Employee of: former employee of Pfizer, M. Whitley Employee of: Pfizer, A. Hill Employee of: Pfizer, Y. Zhang Employee of: Pfizer, D. von Schack: None declared, P. Reddy Employee of: Pfizer, J. Masferrer Employee of: former employee of Pfizer, S. Kamp Grant/research support: Pfizer, J. Guthridge: None declared, A. Thanou: None declared, P. Wu Employee of: Pfizer, T. Paradis Employee of: Pfizer, W. Mounts Employee of: Pfizer, J. James Consultant for: Pfizer, S. Sridharan Employee of: Pfizer DOI: 10.1136/annrheumdis-2014-eular.2788